AXIOLOGICAL CHARACTERISTICS OF KALMYK FAIRYTALES - Karasik, Vladimir I. (Izvestii͡a︡ I͡U︡zhnogo federalʹnogo universiteta. Filologicheskie nauki, 2024)
The paper deals with Kalmyk folk fairytales. These narratives of traditional culture express the main world-view values and norms of behavior as presented in the eternal struggle of the good and the evil. The specific features of the tales analyzed may be summed up in the following characteristics: intellectual and physical competition of the heroes and their enemies, allegory as a status emblem of a wise man, readiness to rescue the friends, understanding the force of fate and taking chances to change it, sacral essence of parents’ will, magic of a loving wife, involvement of the audience into the subject plot development.